Associations of health literacy with risk factors for diabetic foot disease: a cross-sectional analysis of the Southern Tasmanian Health Literacy and Foot Ulcer Development in Diabetes Mellitus Study. Issue 7 (30th July 2019) - Chen, Pamela; Callisaya, Michele; Wills, Karen; Greenaway, Tim; Winzenberg, Tania
Abstract : Objectives: Poor health literacy (HL) is associated with poorer health outcomes in diabetes but little is known about its effects on foot disease. This study was aimed to determine the associations between HL and diabetic foot disease. Design: This is a cross-sectional analysis of baseline data from a prospective study of foot disease. Setting: Attendees of the Royal Hobart Hospital's Diabetes outpatient clinics. Participants: 222 people with type 1 or type 2 diabetes aged >40 years and without a history of foot disease, psychotic disorders or dementia. Measures: Outcomes were peripheral neuropathy, peripheral arterial disease and foot deformity according to published guidelines. The exposure, HL, was measured using the short form Test of Functional Health Literacy in Adults (S-TOFHLA) and the Health Literacy Questionnaire (HLQ). Covariates included demographic characteristics, medical history, psychological measures and foot care behaviour. Results: Of 222 participants, 204 had adequate HL. (Mean (SD) S-TOFHLA scores were 31.9 (6.7)), mean(SD) HLQ scores were 134.4 (18.4)). In univariable but not multivariable analyses, higher S-TOFHLA scores were associated with lower overall risk for foot disease (OR 0.96, 95% CI 0.93 to 0.99) and loss of protective sensation (OR 0.95, 95% CI 0.91 to 0.995). Conclusions: These data provide little support for clinically important impacts of HL on risk factors for diabetic foot disease. However, in the absence of longitudinal data, such effects cannot be ruled out. Longitudinal studies measuring incident foot disease are needed to properly judge the potential for interventions improving HL to reduce the incidence of diabetic foot disease.